National Surveillance of Pediatric Acute Hepatitis of Unknown Etiology, Japan, October 2021–December 2022 - Shogo Otake; Chiaki Ikenoue; Natsu Sudani; Miho Kobayashi; Kensuke Takahashi; Tomoe Shimada; Itsuro Yoshimi; Tomoya Saito; Tomimasa Sunagawa (Emerging Infectious Diseases, 2023)
Pediatric acute hepatitis of unknown etiology has been reported globally since April 2022. In Japan, 139 possible cases with onset dates after October 2021 were reported as of December 2022. Three patients required liver transplants, but none died. Rates of adenovirus positivity (11/125, 9%) were lower than those for other countries.